Inspiring creativity through innovative strategies: the case of Apple Inc. - Mohamad, Noorihsan (2013)
The first iPhone was unveiled by former Apple Inc. CEO Steve Jobs on January 9, 2007 and released on June 29, 2007. Later in the same year, Apple announced that a software development kit (SDK) would be available to third-party developers to guide the programmers to direct their thoughts in the proper course. In less than six months, the App Store contained 500 third-party applications range from business to game applications, entertainment to educational applications. If a mere decade ago, programming was left to tech people with the highest levels of programming knowledge, now programmers of iPhone applications are as young as nine years old. This paper conceptualizes the inventive aspect of Apple's strategy in educating and inspiring the users to be creative and innovative. Here, it is argued that the innovative aspect of Apple Inc. in staggering and restricting product and system development plays a dominant role in inspiring creativity among the users relative to other factors.